ANALYSIS OF THE BLUE OCEAN STRATEGY ENGINEERING APPROACH TO INCREASE SALES IN BUSINESS COMPETITION (CASE TUDI ATAMATI COFFEE BATAM) - Abdullah Merjani; Reva Oktavia Ningrum; Edi Sumarya (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2022)
The development of Coffee shops in Indonesia is still faced with various problems, causing its competitiveness to be weak. One of these problems is the need for the right strategy to be applied by business actors to increase competitiveness.               This study intends to provide advice to entrepreneurs, namely to be able to use the Blue Ocean Strategy as a search method. Blue Ocean Strategy is a strategy or way to conquer competitors through various innovative product offerings. Because the focus of this research is how to design a proposal for the development of observe Coffee using the Blue Ocean Strategy method.               Based on the results of the study, it can be concluded, through the EFAS and IFAS Matrix, the company can find out the position of the company which is currently in quadrant III, which means that there is a need for a change in strategy. Strategies needed Observing Coffee where there are three strategies proposed, the first is a beginner barista school, the second adds to the history of Coffee variants and the third provides a taste table.